Potential of Frangipani (Plumeria alba) Leaves Extract as Ultra Violet Protection - I Gusti Ngurah Agung Windra Wartana Putra; Putu Eka Arimbawa; Ni Putu Rahayu Artini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Sunlight is the source of life and energy. Besides that, sunlight also creates skin challenges such as sunburn, pigmentation, wrinkles, dermatitis, aging, and skin cancer. Natural sunscreen protection is a popular and preferred way among various regions of the world to reduce sunlight's harmful effect. This study aimed to determine the potential of frangipani (Plumeria alba) leaves extract in some concentrations as ultraviolet protection. Plumeria alba extract contained secondary metabolites such as flavonoids, phenolics, and alkaloids that function as impeding ultraviolet radiation. This study used an experimental method consisting of four treatments and six replications. This study shows that the extract with concentration 2500; 5000; 7500; and 10000 ppm consecutively have SPF value of 6.24; 12.00; 18.45; and 22.64. It can be concluded the P. alba leaves extract potential as ultraviolet protection.